Evaluation of seroprevalence and seroconversion rates of Toxoplasma gondii infection in female students at Babol University of Medical Sciences, Babol, Iran - Narges Kalantari; Salman Ghaffari; Masomeh Bayani; Marjan Nouri; Yousef Yahyapour (Babol University of Medical Sciences, 2017)
Objectives: The primary infection of pregnant women by Toxoplasma gondii can cause severe complications in the fetus, and can also lead to neurological complications. The aim of the present study was to determine the seroprevalence and seroconversion rates of Toxoplasma gondii in female students who were at childbearing age in Iran. Methods: This cross sectional study was performed on female students at Babol University of Medical Sciences (Babol, Iran) over a three-year period between 2012 and 2014. Two ml blood sample was obtained from volunteers, and the specific antibodies (IgG) to T. gondii were detected by Enzyme-Linked Immunosorbent Assay. Second, the blood samples obtained from seronegative cases were used to evaluate the seroconversion during a year. Results:  The mean age of the subjects was 21±2.2, ranging from18 to 35 years. Overall, 28% of the participants were positive and 232 (72%) were negative for anti-Toxoplasma antibodies (IgG). The rate of this infection was higher among female students from Mazandaran province (31.7% vs 12.5%) (P=0.031). Based on the results of Enzyme-Linked Immunosorbent Assay, the seroconversion rate of Toxoplasma infection among female students was estimated to be 2.5%. Conclusion: This study found a noticeable rate of seroconversion in female students. Therefore, there is an urgent need for a national screening project to determine the seroconversion rate of Toxoplasma infection in women at childbearing age, particularly pregnant women from all over Iran.